Improved water vapour retrieval from AMSU-B and MHS in the Arctic - Arantxa M. Triana-Gómez; Georg Heygster; Christian Melsheimer; Gunnar Spreen; NEGUSINI, MONIA; Boyan H. Petkov (Atmospheric Measurement Techniques, 2020)
Monitoring of water vapour in the Arctic on long timescales is essential for predicting Arctic weather and understanding climate trends, as well as addressing its influence on the positive feedback loop contributing to Arctic amplification. However, this is challenged by the sparseness of in situ measurements and the problems that standard remote sensing retrieval methods for water vapour have in Arctic conditions. Here, we present advances in a retrieval algorithm for vertically integrated water vapour (total water vapour, TWV) in polar regions from data of satellite-based microwave humidity sounders: (1) in addition to AMSU-B (Advanced Microwave Sounding Unit-B), we can now also use data from the successor instrument MHS (Microwave Humidity Sounder), and (2) artefacts caused by high cloud ice content in convective clouds are filtered out. Comparison to in situ measurements using GPS and radiosondes during 2008 and 2009, as well as to radiosondes during the NICE2015 campaign and to ERA5 reanalysis, show the overall good performance of the updated algorithm.